Teaching Electronic Music: Cultural, Creative, and Analytical Perspectives - Stevens, Blake (New York Abingdon, Oxon Routledge, 2022)
"Teaching Electronic Music offers innovative and practical techniques for teaching electronic music in a wide range of classroom settings. Across a dozen essays, an array of contributors-including musicologists and ethnomusicologists, art historians and music theorists, performers and composers-reflect on the challenges of teaching electronic music, highlighting pedagogical strategies while addressing questions such as: What can instructors do to expand and diversify musical knowledge? Can the study of electronic music foster critical reflection on technology? What are the implications of a digital culture that allows so many to be producers of music? How can instructors engage students in creative experimentation with sound? Electronic music presents unique possibilities and challenges to instructors of music history courses, calling for careful attention to creative curricula, historiographies, repertoires, and practices. Teaching Electronic Music features practical models of instruction as well as paths for further inquiry, identifying untapped methodological directions with broad interest and wide applicability"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Electronic music; Music education; Teaching